2013
DOI: 10.1055/s-0033-1339495
|View full text |Cite
|
Sign up to set email alerts
|

2,4,6-Tris[(4-dichloroiodo)phenoxy)]-1,3,5-triazine as a New Recyclable Hypervalent Iodine(III) Reagent for Chlorination and Oxidation Reactions

Abstract: The synthesis of 2,4,6-tris[(4-dichloroiodo)phenoxy)]-1,3,5-triazine, as a new recyclable nonpolymeric analogue of (dichloroiodo)benzene, is achieved in two steps using 2,4,6-trichloro-1,3,5-triazine and 4-iodophenol. The application of 2,4,6-tris[(4-dichloroiodo)phenoxy)]-1,3,5-triazine for the chlorination reaction of various activated arenes, olefin, and 1,3-diketone is demonstrated. The reagent 2,4,6-tris[(4-dichloroiodo)phenoxy)]-1,3,5-triazine can be applied also for the oxidative synthesis of 1,3,4-oxad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…In our procedure, a broad scope not only in the aromatic ring was explored, but also the groups bonded to the oxygen were included. Thus, we found that acetyl, benzyl, pivaloyl or even propargyl groups were tolerated (33)(34)(35)(36), nevertheless, the chemical yields decreased from 93 % to 62-75 %, presumably due to their steric hindrance. Additionally, the methyl or formyl groups (39,40) in the phenolic ring as well as benzimidazolones (41), carbazole (42) and even pharmacologically active drugs such as naproxen (43) or paracetamol (44) were brominated in good to excellent yields.…”
Section: Bromination Of Phenols With the Pidaà Albr 3 Systemmentioning
confidence: 78%
“…In our procedure, a broad scope not only in the aromatic ring was explored, but also the groups bonded to the oxygen were included. Thus, we found that acetyl, benzyl, pivaloyl or even propargyl groups were tolerated (33)(34)(35)(36), nevertheless, the chemical yields decreased from 93 % to 62-75 %, presumably due to their steric hindrance. Additionally, the methyl or formyl groups (39,40) in the phenolic ring as well as benzimidazolones (41), carbazole (42) and even pharmacologically active drugs such as naproxen (43) or paracetamol (44) were brominated in good to excellent yields.…”
Section: Bromination Of Phenols With the Pidaà Albr 3 Systemmentioning
confidence: 78%
“…A number of oxidative systems have been used for this purpose. They include o ‐iodoxybenzoic acid (IBX), 2,4,6‐tris[(4‐dichloro‐iodo)phenoxy]‐1,3,5‐triazine, the I 2 /O 2 /H 2 SO 4 system, CAN, Oxone, NBS, DDQ, t BuONO, pentylpyridinium tribromide, and air oxygen in the presence of organocatalyst (Table ). Unfortunately, this strategy is suitable only for the synthesis of 1,2,4‐thiadiazoles with the same alkyl or aryl substituents at the 3‐ and 5‐positions and without any functional groups in the thiadiazole ring.…”
Section: Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Compared to the reactions of (dichloroiodo)benzene 1 or analogous (dichloroiodo)arenes under similar conditions, the (dichloroiodo)pyridine reagents showed better reactivity and higher yields. [32][33][34] Among the chlorination reactions, the reactions of 4-(dichloroiodo)pyridine 13 gave the lowest yields because of the low solubility of this reagent in methylene chloride. Finally, we have demonstrated that 2-(dichloroiodo)-3-propoxypyridine 9 can be used as a recyclable reagent.…”
Section: Cl1mentioning
confidence: 99%